Impact of Media Stimulus Health Promotion Videos on Adolescents Risk of Smoking - Djaafar, Nurseha; Kolompoy, Jane Anita; Taaropetan, Chrisna Niklas; Memah, Herlina Patrise; Djaafar, Tjitrowati; Tambuwun, Semuel (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Adolescence is a transitional period, which causes physical, psychological, and social changes. Such changes tend to lead to susceptibility to delinquency in adolescents. One of delinquency begins with smoking behavior, the impact of nicotine on cigarettes can reduce the concentration and memory of adolescents, make someone become an addict or dependent on cigarettes, and can be a gateway to drug entry. Efforts to prevent smoking behavior can be carried out promotive actions through health education using Video Media, to improve good behavior towards preventing adolescent smoking risks. Basic Health Research in 2018 shows a high number of Indonesians who smoke. The number of active smokers of the population aged more than 15 years is 33.8%. Of these, 62.9% of men and 4.8% of women, meaning that two in three men are active smokers. The prevalence of smoking cases in adolescents of school aged 10 to 19 years has increased by 9.1%. In Talaud Islands District the data of daily smokers is 18.40%, smokers not every day 3.63%, do not smoke 77.78%, do not know about cigarettes 0.18%. This study aims to determine the effect of health promotion media stimulus, and smoking risk videos on adolescent behavior. The research method uses a quasi-experimental research design with Pretest and Posttest design with a Control Group Design. The study respondents were adolescents at risk of smoking with a category of 13 to 21 years with a sample of 80 respondents. Data analysis using statistical Wilcoxon signed rank test and significance level p<0.05. 95% confidence level. The results of this study showed a significant value (2-tailed) of <0.000 which means there is a significant effect of stimulus interventions media promotion health video smoking risk on adolescent behavior. The conclusion of this study shows that health promotion video media has an effect as a stimulus on the risk and dangers  of smoking in adolescents.